Hydrothermal Synthesis and Hydrogen Sensing Properties of Nanostructured SnO2 with Different Morphologies - Weigen Chen (Journal of Nanomaterials, 2014)
In this work, nanoscale SnO2 with various geometrical morphologies, including pine needle-like, sphere-like, sheet-like, grape-like nanostructures, was prepared via a facile hydrothermal process. Microstructures and morphologies of all the as-synthesized products were characterized by X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM). Meanwhile, the specific surface areas of the as-prepared SnO2 nanostructures were determined by Brunauer-Emmett-Teller (BET) analysis. Gas sensors were fabricated and their gas sensing properties towards hydrogen were systematically investigated. The results indicate pine needle-like SnO2 structure exhibits exclusive better gas sensing performances to hydrogen than the other morphologies, which can be attributed to its novel shape with a large specific surface area. Such an unexpected morphology is a promising candidate for the use of SnO2 as a gas sensing material in future hydrogen sensor applications.